The Effects of Ischemia During Rest Intervals on Bar Velocity in the Bench Press Exercise With Different External Loads - Jarosz, Jakub; Trybulski, Robert; Krzysztofik, Michał; Tsoukos, Athanasios; Filip-Stachnik, Aleksandra; Zajac, Adam; Bogdanis, Gregory C.; Wilk, Michal (Frontiers in Physiology, 2021)
The main aim of the present study was to evaluate the acute effects of ischemia used during rest periods on bar velocity changes during the bench press exercise at progressive loads, from 20 to 90% of 1RM. Ten healthy resistance trained men volunteered for the study (age = 26.3 ± 4.7 years; body mass = 89.8 ± 6.3 kg; bench press 1RM = 142.5 ± 16.9 kg; training experience = 7.8 ± 2.7 years). During the experimental sessions the subjects performed the bench press exercise under two different conditions, in a randomized and counterbalanced order: (a) ischemia condition, with ischemia applied before the first set and during every rest periods between sets, and (b) control condition where no ischemia was applied. During each experimental session 8 sets of the bench press exercise were performed, against loads starting from 20 to 90% 1RM, increased progressively by 10% in each subsequent set. A 3-minutes rest interval between sets was used. For ischemia condition the cuffs was applied 3 minutes before the first set and during every rest period between sets. Ischemia was released during exercise. The cuff pressure was set to ~80% of full arterial occlusion pressure. The two-way repeated measures ANOVA showed a statistically significant interaction effect for peak bar velocity (p = 0.04) and for mean bar velocity (p = 0.01). There was also a statistically significant main effect of condition for peak bar velocity (p < 0.01) but not for mean bar velocity (p = 0.25). The post hoc analysis for interaction showed significantly higher peak bar velocity for the ischemia condition compared to control at a load of 20%1RM (p =0.007) and at a load of 50%1RM (p = 0.006). The results of the present study indicate that ischemia used before each set even for a brief duration of <3 min, has positive effects on peak bar velocity at light loads, but it is insufficient to induce such effect on higher loads.